Electrospinning Enables Opportunity for Green and Effective Antibacterial Coatings of Medical Devices - Saverio Caporalini; Bahareh Azimi; Samir Zergat; Mahdi Ansari Chaharsoughi; Homa Maleki; Giovanna Batoni; Serena Danti (Journal of Functional Biomaterials)
The growing antimicrobial resistance and the increasing environmental concerns associated with conventional antibacterial agents have prompted a search for more effective and sustainable alternatives. Biopolymer-based nanofibers are promising candidates to produce environment-friendly antibacterial coatings, owing to their high surface-to-volume ratio, structural adaptability, and tunable porosity. These features make them particularly well-suited for delivering antimicrobial agents in a controlled manner and for physically modifying the surface of medical devices. This review critically explores recent advances in the use of electrospun fibers enhanced with natural antimicrobial agents as eco-friendly surface coatings. The mechanisms of antibacterial action, key factors affecting their efficacy, and comparisons with conventional antibacterial agents are discussed herein. Emphasis is placed on the role of a “green electrospinning” process, which utilizes bio-based materials and nontoxic solvents, to enable coatings able to better combat antibiotic-resistant pathogens. Applications in various clinical settings, including implants, wound dressings, surgical textiles, and urinary devices, are explored. Finally, the environmental benefits and prospects for the scalability and sustainability of green coatings are discussed to underscore their relevance to next-generation, sustainable solutions in healthcare.